Directional Overcurrent Relay Based Adaptive Protection Techniques For Distribution Networks - Tamyiğit, Furkan Ahmet; Shobole, Abdulfetah Abdela; Güneş, İbrahim; Wadi, Mohammed; Wadi, Mohammed; Tamyiğit, Furkan Ahmet; Shobole, Abdulfetah Abdela (Livre de Lyon, 2025)
Nowadays, electricity distribution networks tend to grow with the increasing the energy demand. Thus, the number of distributed generation sources (DGR) in electricity distribution networks is increasing in order to meet the energy demand. DGRs are known as Renewable Energy Sources (RES) with intermittent operation nature such as wind energy (Wadi et al., 2023), solar energy (Wadi, Jouda, et al., 2024), fuel cells, battery storage systems and other sources. Today, as the number and size of these distributed generation sources increase, electricity distribution networks are evolving to become more reliable and sustainable. Integrating DGRs into distribution networks (DGRs) reduces the dependence of loads on long distantance generation sources and helps to minimize transmission losses by reducing the activity of transmission systems. However, DGRs cause some technical problems in addition to the advantages they provide to transmission and distribution systems. These technical problems are; power quality problems (Razmi et al., 2023), adverse load flow (Roy & Pota, 2015), technical losses, grid stability and reliability problems (Ndawula et al., 2019) and protection system difficulties (El Idrissi et al., 2021) stand out. As focused on in this chapter, the difficulties experienced in the protection system of the distribution network with the increase in DGRs; Reverse Power Flow (RPF), increase in short-circuit currents (Meskin et al., 2020), bi-directional power flow (Alcala- Gonzalez et al., 2022), fault impedance and protection blindness (Tariq et al., 2021) and impairment of protection coordination (Yousaf et al., 2021). In particular, with the increase in distributed energy resources, protection coordination structures in electrical grids are becoming invalid.

Conclusion: The presented adaptive protection algorithms are analyzed on IEEE 14 bus test network with DIgSILENT PowerFactory software and DPL language. LAPCS and MASAPCS algorithms meet all criteria in terms of speed, redundancy, selectivity and economy. However, it is calculated that MASAPCS algorithm clears the fault current 54% faster with main protection relays and 44% faster with backup protection relays compared to LAPCS. Therefore, in Table 11, the operating performances of MASAPCS algorithm are compared with other algorithms in the literature. While MASAPCS algorithm offers simple configuration convenience in complex networks depending on the innovative technologies of digital relays; LAPCS algorithm is a centralized adaptive protection philosophy that responds to dynamic changes in meshed based networks. While MASAPCS algorithm is based on relay technology; LAPCS is based on network type. Although both algorithms have advantages according to network type or relay technology or DGRs number, their operating performances are presented in Tables 5, 6, 7, 10.
Book title: INNOVATIONS AND APPLICATIONS OF ARTIFICIAL INTELLIGENCE IN ELECTRICAL AND ELECTRONICS ENGINEERING -- Editors: Mohammed WADI & Mohammed SALEMDEEB & Mohammed JOUDA -- copyright © 2025 by Livre de Lyon -- e-ISBN: 978-2-38236-821-3 -- DOI: 10.5281/zenodo.15093100.